2020
DOI: 10.1680/jgeot.18.p.303
|View full text |Cite
|
Sign up to set email alerts
|

Vertical static and dynamic pile-to-pile interaction in non-linear soil

Abstract: A vertically loaded floating pile in clay affects a neighbouring pile by increasing the latter's displacement due to its own load. As a result, a group of rigidly capped piles exhibits a force/settlement ratio (‘vertical stiffness’) that is smaller than the sum of the individual stiffnesses of each pile – ‘efficiency’ in static stiffness less than 1. However, under dynamic steady-state loading the response of the pile group is an oscillatory function of frequency, and at certain frequencies a complete reversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The pile-soil interface has been considered to be an important aspect for both static and dynamic impedance of pile groups. However, recent studies [33][34][35] have shown that separation effects are of less significance when plasticity is considered. Also, this study only assesses the kinematic response.…”
Section: Elements Boundaries and Solution Schemesmentioning
confidence: 99%
“…The pile-soil interface has been considered to be an important aspect for both static and dynamic impedance of pile groups. However, recent studies [33][34][35] have shown that separation effects are of less significance when plasticity is considered. Also, this study only assesses the kinematic response.…”
Section: Elements Boundaries and Solution Schemesmentioning
confidence: 99%
“…Despite the computation attractiveness of elastic modelling, in reality soil exhibits nonlinear response even at small strains. During strong earthquakes, inelastic soil response is inevitable and can affect dynamic SSI to a great extent [43][44][45]. It is therefore crucial to evaluate its influence on the protective role of resonant metamaterials.…”
Section: Nonlinear Structure On Nonlinear Soilmentioning
confidence: 99%
“…For dynamic inertial loading at their top under elastic conditions in homogeneous soil the interaction between the two caissons would be significant (Dobry and Gazetas 1988). However, soil nonlinearity that develops in this case, drastically reduces such interaction (Gazetas et al 2021;Kanellopoulos and Gazetas 2020;Radhima et al 2021). Moreover, the "kinematic" effects are prominent in our case, because in addition to the direct seismic wave loading there is indirect loading from the lateral soil movement.…”
Section: Initial "As-built" Modelmentioning
confidence: 99%